Inhibition of C6 Glioma Cell Proliferation by Au(III) and Pt(II) Complexes of 1,10-Phenanthroline-5,6-dione - Dikmen, Miris; Benkli, Kadriye; Ozturk, Yusuf (Asian Journal of Chemistry, 2011)
In this study, we studied the antiproliferative effecs of Au(III) and Pt(II) metal complexes of 1,10-phenanthroline-5,6-dione and cisplatin on rat glioma C6 cells. The antiproliferative effects were evaluated by MTT ((3,4,5-dimethylthiazol-2-yl)-2-5-diphenyltetrazolium bromide) cell proliferation assay. We determined that Au(III) and Pt(II) metal complexes of 1,10-phenanthroline- 5,6-dione and cisplatin have significant the time- and concentration-dependent antiproliferative effects on C6 glioma cells. Cell proliferation was significantly decreased by 5-100 μM of Au(III) and Pt(II) metal complexes at 24 and 48 h. Especially, an inhibition in the cancer cell proliferation was observed Au(III) metal complex being higher than that with Pt(II) metal complex. The present study demonstrates a powerful in vitro antitumor action of Au(III) metal complex of 1,10-phenanthroline-5,6-dione on C6 glioma cells.